Fly High, Katie - Manushkin, Fran.; Lyon, Tammie (North Mankato, MN : Capstone Picture Window Books, 2014)
Katie is flying to Florida to visit her grandmother, but she has never been on an airplane before.
Accelerated Reader AR
Keywords: Airplanes -- Juvenile fiction; Air travel -- Juvenile fiction; Chinese Americans -- Juvenile fiction